Llnguopalatal contact differences between Japanese geminate and singleton stops - Kochetov, Alexei (Canadian Acoustics, 2012)
Japanese is known to exhibit a phonemic contrast between geminate and singleton consonants. This contrast has received considerable attention in phonetic literature, with most studies focusing on its most salient, durational properties - differences between geminated and singletons in the duration of the consonant and the preceding or following vowel. The results of this preliminary study confirm the hypothesis that durational differences in the production of Japanese geminate/singleton stops can be accompanied by differences in the degree of contact. The longer geminates tend to be articulated with a tighter constriction, compared to the shorter and weaker-articulated singletons. To conclude, the current study presented some evidence for the role of degree of contact in the realization of the Japanese geminate and singleton stops, contributing to the growing body of work on non-durational acoustic and articulatory correlates of the contrast.